If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(x-6)-(2x-9)=12-2(4-x)
We move all terms to the left:
3(x-6)-(2x-9)-(12-2(4-x))=0
We add all the numbers together, and all the variables
3(x-6)-(2x-9)-(12-2(-1x+4))=0
We multiply parentheses
3x-(2x-9)-(12-2(-1x+4))-18=0
We get rid of parentheses
3x-2x-(12-2(-1x+4))+9-18=0
We calculate terms in parentheses: -(12-2(-1x+4)), so:We add all the numbers together, and all the variables
12-2(-1x+4)
determiningTheFunctionDomain -2(-1x+4)+12
We multiply parentheses
2x-8+12
We add all the numbers together, and all the variables
2x+4
Back to the equation:
-(2x+4)
x-(2x+4)-9=0
We get rid of parentheses
x-2x-4-9=0
We add all the numbers together, and all the variables
-1x-13=0
We move all terms containing x to the left, all other terms to the right
-x=13
x=13/-1
x=-13
| N/6-2/3=n/3+5/6 | | 9=x2+2 | | 11x+36+11x+36=17x+77 | | 8(1-x)-3(2x-7)=1 | | 10=x=-6x+73 | | 6+1/5b=3/10 | | 6x-15=3x+17=6x-13 | | 2/3*(x+4)=14 | | 5x+9+6x=180 | | (2/3)*(x+4)=14 | | 2*5w-6+1*5w-8=10 | | 15m=-69 | | 2(3x-4)=3(2-5x) | | 25w-6+15w-8=19 | | 14m=-81.2 | | -8=-0.2p | | A+5+8a-5=180 | | 6-4(5x-3)=-2 | | -30=-0.6p | | 2=11−3g | | -1=-5y+3(y+3) | | 5(x-1)=12x | | -6j-9=-7j | | -3m=-7-4m | | 11=15−2c | | 3-5g=-2g | | 13=3c−5 | | -4.5x=72 | | 2x+1/3=7x+3/15 | | y/2=90 | | 1=v+1 | | 2d−5=5 |